2019
DOI: 10.7717/peerj.6867
|View full text |Cite
|
Sign up to set email alerts
|

Moderating factors influence the relative age effect in Australian cricket

Abstract: Background The relative age effect is a commonly occurring phenomenon whereby there is a tendency for relatively older players to be over-represented during high level competitions. This effect is often seen to diminish as player’s age, however, there has been far less investigation on other potential moderating factors. Method This study investigated the impact of the relative age effect, and potential moderating factors, within the talent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
(44 reference statements)
2
9
1
1
Order By: Relevance
“…Second, cricketers in this study were categorized based on whether they competed in a younger age or older age national competition, which relies on chronological age cutoffs. Previous research has highlighted that selection in these competitions can heavily bias the sample population toward relative older players (Connor et al, 2019). Finally, the nature of this study does not allow for the analysis of explanatory factors of various batting stances.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, cricketers in this study were categorized based on whether they competed in a younger age or older age national competition, which relies on chronological age cutoffs. Previous research has highlighted that selection in these competitions can heavily bias the sample population toward relative older players (Connor et al, 2019). Finally, the nature of this study does not allow for the analysis of explanatory factors of various batting stances.…”
Section: Discussionmentioning
confidence: 97%
“…While there is evidence that left-handedness—and perhaps a “reversed stance”—may be advantageous at the elite level of competition ( Mann et al, 2016 ), much less is known about the age, gender, or performance level at which these advantages might emerge, particularly as other talent selection bias has been previously highlighted in cricket ( Connor et al, 2019 ). If the negative frequency-dependent hypothesis were apparent, then it might be reasonable to expect the advantage of the left-handed cricket batters to increase over time due to a progressive accrual of experience competing against right vs. left-handed opponents.…”
Section: Introductionmentioning
confidence: 99%
“…There is compelling evidence that the RAE phenomenon as such reduces from junior to senior level, for example, likely due to the reduction in birth-month-related relative age differences with increasing age (Cobley et al, 2009 ). Investigating RAE in male- and female-talented Australian cricketers, Connor et al ( 2019 ) suggested that birth distribution was skewed toward quartile 1 in both left- and right-handed batters and bowlers at the younger age groups (e.g., under 15, under 17), but no longer in left- and occasionally in right-handed players at older age groups (i.e., under 19 and state level). Consequently, provided that the RAE phenomenon is more pronounced and that left-handedness is also relevant to performance at the junior level, the hypothesized effect of athletes' handedness in conjunction with birth month might show through more clearly in that particular age group.…”
Section: Study 2: Relative Age Effects and Handedness In World-class mentioning
confidence: 99%
“…In view of the performance benefits ascribed to lefthandedness in interactive sports, it has been suggested that left-handedness may be associated with reduced likelihood of suffering from selection inequalities like RAE (Wattie et al, 2015). Evidence in at least partial support of this notion can primarily be inferred from data on interactive team sports like handball (Schorer et al, 2009), cricket (Connor et al, 2019), baseball (Zhang et al, 2018, and water polo (Barrenetxea-Garcia et al, 2019). Birth distribution was found to be heavily skewed toward quartile 1 (January-March) in right-but not left-handed backcourt players from the German first handball league for the seasons 2004/2008(Schorer et al, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Collins et al, 2016a) as they inevitably will. This is especially important as there is a significant body of robust evidence to show that those performers who have early advantages fall away in increasing numbers the higher up the pathway they go (McCarthy, Collins & Court, 2016;Connor, Renshaw & Doma, 2019).…”
Section: Experience Of Functional Variability When Deployed Effectivmentioning
confidence: 99%